The sugar code: functional lectinomics - Gabius, Hans-Joachim; André, Sabine; Kaltner, Herbert; Siebert, Hans-Christian (BBA - General Subjects, 2002)
Analysis of the genome and proteome assumes the focus of attention in efforts to relate biochemical coding with cell functionality. Among other chores in energy metabolism, the talents of carbohydrates to establish a high-density coding system give reason for a paradigmatic shift. The sequence complexity of glycans and glycan-processing enzymes (glycosyltransferases, glycosidases and enzymes introducing substituents such as sulfotransferases), the growing evidence for the importance of glycans from transgenic and knock-out animal models and the correlation of defects in glycosylation with diseases are substantial assets to portray oligosaccharides as code words in their own right. Matching the pace of progress in the work on glycoconjugates, the increasing level of refinement of our knowledge about lectins (definition of this term: carbohydrate-binding proteins, excluding sugar-specific antibodies, receptors of free mono- or disaccharides for transport or chemotaxis and enzymes modifying the bound carbohydrate) epitomizes the sphere of action of the sugar code ( functional lectinomics). It encompasses, among other activities, intra- and intercellular transport processes, sensor branches of innate immunity, regulation of cell–cell (matrix) adhesion or migration and positive/negative growth control with implications for differentiation and malignancy. The Q & A approach taken in this review lists a series of arguments in a stepwise manner to make the reader wonder why it is only a rather recent process that the concept of the sugar code has taken root in deciphering the mechanistic versatility of biological information storage and transfer.